Scoring system reliabilty in Vancouver 2010 Winter Olympic Games Halfpipe-Snowboarding Competition - Jesús Muñoz Jiménez; José Antonio Pérez Ruiz; Miguel Hernández Mocholi; Daniel Collado Mateo; Kiko F. León Guzmán (Federación Extremeña de Balonmano; University of Extremadura, 2016)
Snowboarding-Halfpipe is a high performance sport discipline which is included in Winter Olympic Games program. Competition system is based on the observation of riders' technical performance, for which judges take as reference the official manual that collects principal aspects of exercises scoring. Given the inherent characteristics of this sport, in which performance is based on the observation ability of judges, training and experience of this judges is crucial in order to turn the observation into a measurement as objective as possible. Accordingly, this article aims to quantify reliability indices between judges' scores as well as their relationship to the gender, the presence of falls and the number of hops. The study sample comprised all the exercises developed during the final two rounds of the Vancouver 2010 Olympic Winter Games, both male (n=24) and female competition (n=22). Results showed that the reliability between judges is excellent (Round 1: ICC=0,985, αC=0,997, Round 2: ICC=0,991, αC=0,998), regardless of gender, presence of falls or the number of hops.